2021
DOI: 10.3390/su131810345
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Propagation and ISSR-Based Genetic Identification of Genotypes of Ilex aquifolium ‘Agrifoglio Commune’

Abstract: The market demand for interesting varieties and cultivars of Ilex aquifolium necessitates the exploration and sustainable exploitation of plant individuals thriving in nature without human care. In this work, an effort was made to develop a simple and reliable protocol for vegetative propagation of I. aquifolium plants, with desirable-for-market characteristics, grown in a mountain area of Halkidiki, Greece, and at the same time to proceed with their genetic identification using molecular markers. From these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…However, when the acclimation stage is completed, the plant will be in a new growing environment where the humidity, temperature and air temperature are no longer in a constant state (do Vale 2019). Acclimation of S. nageliana by the roots, which ensures retention of the good traits of the mother plant to the offspring (Tsaktsira 2021) and mitigating possible changes in the production of secondary metabolites, is one of the biggest challenges in the cultivation and management of this potentially medicinal Smilax species (Soares 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, when the acclimation stage is completed, the plant will be in a new growing environment where the humidity, temperature and air temperature are no longer in a constant state (do Vale 2019). Acclimation of S. nageliana by the roots, which ensures retention of the good traits of the mother plant to the offspring (Tsaktsira 2021) and mitigating possible changes in the production of secondary metabolites, is one of the biggest challenges in the cultivation and management of this potentially medicinal Smilax species (Soares 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to increase rooting ability of woody species, auxins are applied to the basal part of the stem cuttings where adventitious root initiation and development will take place. Studies have shown that the use of auxins is essential for obtaining the maximum number of rooted cuttings in a short period of time (Metaxas et al, 2004;Bayraktar et al, 2018;Kostas et al, 2021;Tsaktsira et al, 2021). The indole-3-butyric acid (IBA) is the most commonly used auxin for rooting in commercial propagation; other auxins often used are indole-3-acetic acid (IAA) and naphthalene acetic acid (NAA) (De Klerk et al, 1999;Hartmann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Seed germination may be poor or erratic due to dormancy [ 3 ]; moreover, the viability of seeds is very low [ 4 ]. In the horticultural industry, vegetative propagation is the most popular method, as it is cheaper, easier and faster than sexual reproduction [ 5 ]; the plants produced are clones that maintain the morpho-physiological and genetic characteristics of the stock plants, uniformity and earliness of production [ 6 ].…”
Section: Introductionmentioning
confidence: 99%